St. Thomas Aquinas’ Doctrine of Christ’s Descent into Hades and its implications for African Ancestor Christological discourse - Boaheng, Isaac (Acta theologica, 2024)
The statement "he [Christ] descended into Hades" in the Apostles’ Creed has generated theological debate concerning the nature and purpose of the descent and the relationship of Christ to ancestors. Given St. Thomas Aquinas’ outstanding contribution to the development of this doctrine, this article explores Aquinas’ contributions to the doctrine of Christ’s descent into Hades. It then critiques ancestor Christology through the lens of the descent doctrine. A desktop research approach is used to gather and analyse data from journal articles, books, and theses. The article argues that Christ died in place of sinful humanity and bore the total punishment for sin; therefore, there is no sacrifice for salvation except that which Christ offered. This emphasises that salvation is solely through Christ, and no rituals, sacrifices, or ancestors can replaceHis redemptive work. The article also asserts that Christ,as the Son of God, surpasses any human ancestor inimportance and power, making ancestor Christology invalid. It encourages Akan Christians to place their faith solely in Christ.